Dielectric thermal analysis as a tool for quantitative-evaluation of the viscosity and the kinetics of epoxy resin cure - Shigue, Carlos Y.; dos Santos, Rafaela G. S.; de Abreu, Mariane M. S. P.; Baldan, Carlos A.; Robin, Alain L. M.; Ruppert-Filho, Ernesto (Institute of Electrical and Electronics Engineers (IEEE), 2006)
Dielectric thermal analysis has been proved as a valuable tool for monitoring the epoxy curing process and the related rheological properties in the fabrication of polymer-matrix composite materials. This technique also has the potential to be applied in the monitoring of magnet impregnation processes as well as in quality control. In this work we present the quantitative evaluation of the viscosity changing and the curing kinetics for a commercial Stycast epoxy resin system at different temperatures through the impedance analysis. The results showed correlation between the real component of the complex impedance and the isothermal reaction extent. Comparing the dielectric analysis result with the viscosity measured by rotational rheometer we observed a similar behavior reported for dynamic mechanic analysis. The results comparison have shown that the kinetics parameters obtained from DSC and DETA analysis showed different sensitivities related to the characteristics of curing stages. We concluded that the dielectric thermal analysis should be applied in quantitative evaluation of cure kinetics.
Keywords: complex impedance; curing extent degree; epoxy curing; dielectric analysis; thermal analysis; viscosity